MORPHOLOGICAL ANALYSIS OF STUDENTS’ WRITING - Fitriyeni, Fitriyeni (English Education Department at FKIP Nommensen University, 2024)
Morphology is one of the important studies in linguistics that focuses on the words and the forming of the words from smallest pieces. This study explored morphological issues in students’ writings about their favorite person and best friend. Data were collected from students’ writing products that belongs to twenty five elementary students of fifth grades. The collected data were analyzed to examine the morphological errors encountered by the students in the rank of morphemes, words, phrases, and sentences The types of errors include omission, overused, misordering, misplacement, and misselection in the free morpheme (lexical and functional) and bound morpheme (inflection and derivation) elements. This research revealed that the participants contributed morphology errors in noun, verb, adjective, and adverb. Second, the most frequent type of morphological errors contributed by participants was misselection. The students have difficulties in understanding the formation and function of words due to the interference of their first language, the low proficiency of English words and structure, and their low practice of writing in the target language. It is expected that the teachers to use interesting technique of teaching and learning English to assist the students’ practices of the target language, and also frequently make corrections and explanations of the students’ writing for them to get clear and specific understanding of the aspect of morphology.